ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2021
DOI: 10.1109/icassp39728.2021.9414034
|View full text |Cite
|
Sign up to set email alerts
|

Contact Tracing Enhances the Efficiency of Covid-19 Group Testing

Abstract: Group testing can save testing resources in the context of the ongoing COVID-19 pandemic. In group testing, we are given n samples, one per individual, and arrange them into m < n pooled samples, where each pool is obtained by mixing a subset of the n individual samples. Infected individuals are then identified using a group testing algorithm. In this paper, we use side information (SI) collected from contact tracing (CT) within nonadaptive/single-stage group testing algorithms. We generate data by incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Observe that the upper and lower bounds match as α * → 0. More generally, recent results in [16], [17] demonstrated that (9) that is tight for general designs (i.e., there exists a matching achievability result), whereas Bernoulli designs cannot do better than (8), so they are mildly suboptimal in terms of the dependence on α * .…”
Section: B Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Observe that the upper and lower bounds match as α * → 0. More generally, recent results in [16], [17] demonstrated that (9) that is tight for general designs (i.e., there exists a matching achievability result), whereas Bernoulli designs cannot do better than (8), so they are mildly suboptimal in terms of the dependence on α * .…”
Section: B Related Workmentioning
confidence: 99%
“…Two algorithms in [8] are proposed for exploiting information from contact tracing with two different test models. In particular, in the case of a binary-valued testing model (as we consider), they propose a Generalized Approximate Message Passing (GAMP) algorithm based on a dynamic infection model with known infection times and physical proximity levels.…”
Section: B Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The paper leverages the structure of H = (V, E) to maximize the efficiency of the group testing algorithms in the adaptive, non-adaptive, and probabilistic settings. A few related papers [9], [10] focus on leveraging side-information (e.g., that can be obtained from contact tracing) to make the decoding algorithm faster. Finally, graph-constrained group testing, a variant of the group testing problem where the tests must conform to constraints imposed by a graph, is considered, e.g., in [11]- [13].…”
Section: Introductionmentioning
confidence: 99%